Exposição ocupacional a material biológico em ambiente de ensino odontológico - Helenaura Pereira M Carvalhais (2006)
The objectives of this cross-section study were to determine the prevalence of the occupational accidents to potentially infector biological material and the reporting, to estimate risk factors associates to the exposition to the blood and the underreporting in a dental teaching environment. The data were collected by an auto-applicable questionnaire. The rate of return was 86.4 percent. The sample consisted of 286 regularly registered students in disciplines clinics, what corresponds to the six last periods of learning semesters. The averageage was 22.4 years. Analysis were carried through descriptive, univariable and regression simple and multiple logisitc (Stepwise Forward Procedure), adopting the level of significance p 0.05. Expositions to potentially infector biological material were reported Expositions to potentially infector biological material were reported by 167 individuals (58.4 percent), being 102 percutaneous exposure and in mucous (35.6 percent). The underreporting tax was 71.9 percent. The multiple expositions tax was 1.8 accidents per displayed student. The multivaried analysis showed that the incomplete use of the Equipment of Individual Protection, disciplines where if they had carried through surgical procedures and handle sharp instruments, more specifically, hollow-bore needles, had been associates independently with the exposition to the blood. The variables that kept statistically associates in a independent way with underreporting of the occupational accidents were not the exposition to blood and the fact of the students considered exposure small or inadequate the protocol adopted for institution. It isrecommended to develop politics of procedures revision to reduce the frequency of the occupational expositions, by means of strategies that contemplate the universe of the social representations.